The Relationship between the Cloud Computing Model and Information Technology Infrastructure Library (ITIL) from the Viewpoint of Experts - Isaias Scalabrin Bianchi; Antônio Pinto; Ruben Pereira (Innovar: Revista de Ciencias Administrativas y Sociales)
Cloud Computing is widely recognized as a recent computing paradigm of digital transformation, in which scalable and elastic computational resources are delivered as a service through internet technologies. Understanding the impacts of the Cloud model on how companies organize their processes is essential. This study aims to investigate the main impacts of the Cloud Computing model on the processes within the Information Technology Infrastructure Library (ITIL) framework. A systematic literature review (SLR) was conducted, whose results suggest that certain aspects may be underexplored in the traditional academic literature. Consequently, we conducted qualitative research using semi-structured interviews with ITIL-certified professionals from nine countries. This approach allowed us to collect valuable and in-depth insights, contributing to a better understanding of the subject. Our analysis of the SLR results indicates that several ITIL framework processes have been affected, which may lead to a re-evaluation of the framework. We identified benefits, constraints to innovation, and strategies for creating a sustainable environment when implementing these processes. The findings revealed a scarcity of studies on the relationship between Cloud Computing and ITIL. Perspectives from ITIL professionals provided useful insights into the benefits, constraints, impacts, and affected processes. This study may serve as a valuable resource for ITIL clients, decision-makers, and developers.